A mixed factorial experiment with colors and adaptive web user interfaces to change emotions - Guimarães, Patrícia Deud; Silva, Fernando Miguelão; Ara, Anderson; Neris, Vânia Almeida (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2023: Anais do XXII Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2023)
As each person feels emotions differently, web interactive systems may deliver personalized experiences trying to support users to achieve a desired emotional state. A common way of doing so is by providing user interface (UI) adaptation. However, the impact of such adaptations on the users’ emotions is not thoroughly studied. In this work, we describe a mixed factorial experiment with 44 participants in which each one should perform two tasks on the web: reading and transcription. Emotional data was provided by users through a form and also facial expressions via webcam. We represented the users’ emotional paths while performing the tasks and analyzed the most common emotional paths performed by participants. Although most participants reached their desired emotional state in both the experimental and placebo groups, we did not have statistical evidence to prove that users were more likely to achieve the desired emotion while using the adapted UI.